2020
DOI: 10.1016/j.bionps.2020.100015
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortical alterations of glutamate and GABA neurotransmission in schizophrenia: Insights for rational biomarker development

Abstract: Certain cognitive deficits in schizophrenia, such as impaired working memory, are thought to reflect alterations in the neural circuitry of the dorsolateral prefrontal cortex (DLPFC). Gamma oscillations in the DLPFC appear to be a neural corollary of working memory function, and the power of these oscillations during working memory tasks is lower in individuals with schizophrenia. Thus, gamma oscillations represent a potentially useful biomarker to index dysfunction in the DLPFC circuitry responsible for worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 156 publications
(199 reference statements)
1
20
0
1
Order By: Relevance
“…Ahora se conoce que la hipótesis de dopamina era tal vez una explicación sobresimplificada del funcionamiento cerebral de las personas con psicosis. Ahora se discute sobre otras anormalidades tanto a nivel molecular como de rutas neuronales, no sólo en la dopamina, sino también en la serotonina, el glutamato y el GABA (Schoonover et al, 2020;Stahl, 2018).…”
Section: Anormalidades Neuromolecularesunclassified
“…Ahora se conoce que la hipótesis de dopamina era tal vez una explicación sobresimplificada del funcionamiento cerebral de las personas con psicosis. Ahora se discute sobre otras anormalidades tanto a nivel molecular como de rutas neuronales, no sólo en la dopamina, sino también en la serotonina, el glutamato y el GABA (Schoonover et al, 2020;Stahl, 2018).…”
Section: Anormalidades Neuromolecularesunclassified
“…Glutamate and GABA play a major and well-known role in cognitive deficit in schizophrenia. An imbalance in both neurotransmitters was observed in DLPFC [ 46 ]. This area is associated with working memory—that is, the ability to manipulate information to guide behavior or thought [ 47 ].…”
Section: Etiology Of Neurocognitive Impairmentmentioning
confidence: 99%
“…Although not fully described, changes in other neurotransmitters such as acetylcholine, histamine or dopamine have been reported in schizophrenia-induced cognitive deficit patients [ 46 ]. It has been suggested that there is a relationship between a decrease in striatal dopamine and the observed disruption in cortico-cerebellar-thalamic-cortical circuits in cognitive deficits in schizophrenia [ 65 , 66 ].…”
Section: Etiology Of Neurocognitive Impairmentmentioning
confidence: 99%
“…Postmortem data suggest that GAD67 mRNA translation in the DLPFC has initially decreased through layers 1 to 5, resulting in decreased GAD67 protein levels. 28 It can cause a reduction in the number of neurons in schizophrenia. Based on these studies, it has claimed that the disturbance in GAD67 gene expression occurs exclusively in a specific subset of GABAergic neurons.…”
Section: Dopamine Hypothesismentioning
confidence: 99%